Perancangan Interior Galeri dan Bengkel Lamborghini di Surabaya - Mitchel Philander Liemijanto; Lintu Tulistyantoro; Hendy Mulyono (Intra, 2019)
Lamborghini is an Italian hyper car that attracts everyone who saw it. in Indonesia, there are a lot of people who owned these luxury cars, and most of these Lamborghinis are spread around the major cities in Indonesia, including Surabaya and become a place for designing Showrooms of Lamborghini Surabaya. There is a lot of bourgeoisie in Surabaya, that was very fond of Lamborghini, especially the Lamborghini Aventador, but there is no official community for Lamborghini that based in Surabaya. With the design of this Showroom, the members of Lamborghini Surabaya can have a place that accommodate their needs, with the concept that combines technology and luxury, this design adapts to the user’s conditions that tend to be in a luxurious style. This Showroom can be a solution to the problems that was experienced by the Lamborghini owners in Surabaya.